Asia's environmental movements - Yok-Shiu F. Lee (ed.); So, Alvin Y. (ed.) (London, 1999)
Adopting a comparative perspective, this book traces the social, political, economic and cultural conditions under which environmental movements have emerged, and assesses the transformative capacities of these movements.
Keywords: Environmental policy Asia